2017
DOI: 10.1002/2017ef000625
|View full text |Cite
|
Sign up to set email alerts
|

Emissions embodied in global trade have plateaued due to structural changes in China

Abstract: In the 2000s, the rapid growth of CO2 emitted in the production of exports from developing to developed countries, in which China accounted for the dominant share, led to concerns that climate polices had been undermined by international trade. Arguments on “carbon leakage” and “competitiveness”—which led to the refusal of the U.S. to ratify the Kyoto Protocol—put pressure on developing countries, especially China, to limit their emissions with Border Carbon Adjustments used as one threat. After strong growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 60 publications
0
28
0
1
Order By: Relevance
“…China has been the main engine of growth in global international emission transfers (Peters, Davis, et al, 2012), and since the analysis in this paper was completed, other work by Pan et al (2017) and Mi et al (2017) have shown China's effect on the stagnation of emission transfers. They attribute changes in emission transfers directly to the change in export volumes in the 1997-2007 period, before declines in Chinese emissions intensity and changes to production structure overtook growth in exports post-2007.…”
Section: Introductionmentioning
confidence: 82%
“…China has been the main engine of growth in global international emission transfers (Peters, Davis, et al, 2012), and since the analysis in this paper was completed, other work by Pan et al (2017) and Mi et al (2017) have shown China's effect on the stagnation of emission transfers. They attribute changes in emission transfers directly to the change in export volumes in the 1997-2007 period, before declines in Chinese emissions intensity and changes to production structure overtook growth in exports post-2007.…”
Section: Introductionmentioning
confidence: 82%
“…Some researchers have used SDA to analyze the drivers of China's export‐embodied emissions, including during this period. Xu et al (), Su and Thomson (), and Pan et al () used the SDA approach to analyze the determinants of the changes in China's export‐embodied emissions for 2002–2008, 2006–2012, and 1997–2012, respectively. However, these were all based on single‐region input‐output models, which cannot reflect regional variations and domestic interregional trade.…”
Section: Introductionmentioning
confidence: 99%
“…According to data from the National Bureau of Statistics of China, the average annual growth rates of China's imports and exports from 2002 to 2007 were 24.58% and 28.28%, respectively (NBSC (National Bureau of Statistics of China), 2009). This (Pan et al, 2017). Under the combined influence of these factors, the growth of China's EEI and EEE slowed down, particularly that of China's EEE, and there was negative growth of China's BEET.…”
Section: The Analysis Of China's Eei and Eeementioning
confidence: 96%